Efficiency of the Stool-PCR Test Targeting NADH Dehydrogenase (Nad) Subunits for Detection of Opisthorchis viverrini Eggs - Wansika Phadungsil; Supaporn Pumpa; Kridsada Sirisabhabhorn; Amornrat Geadkaew-Krenc; Rudi Grams; Mathirut Mungthin; Toon Ruang-Areerate; Poom Adisakwattana; Nipawan Labbunruang; Pongsakorn Martviset (Journal of Tropical Medicine)
Opisthorchis viverrini infection is the major parasitic infection problem in Southeast Asian countries, and long-term infection will lead to cholangiocarcinoma (CCA), the bile duct cancer. The early diagnosis of O. viverrini infection may interrupt the progression of the opisthorchiasis and other related illnesses, especially CCA. The current diagnostic procedure is stool examination by microscope-based methods such as direct smear and concentration techniques but it is limited by low parasite egg numbers. The molecular diagnosis prompts the chance to evaluate the light infection with low number of parasite eggs but is currently inconvenient for routine use due to special equipment requirement and unstable sensitivities. Our present study aims to establish the efficiency of OvNad subunits, the mitochondrial gene, for introducing as a potential diagnostic target by conventional PCR, the cheapest and easiest molecular procedure. A total of 166 stool samples were investigated microscopically by the PBS-ethyl acetate concentration technique (PECT); 75 samples were O. viverrini positive with 28 samples that were positive with single parasite (hookworm, A. lumbricoides, S. stercoralis, Taenia spp., and T. trichiura), 11 samples were with mixed infection, and 52 samples were without parasite detection. The detection limits of OvNad subunits were evaluated in artificially spiked samples containing 0, 1, 5, 10, 20, 50, and 100 Ov-eggs. The result suggested that the best detection efficacy was of OvNad5 that had exact detection limits at only 5 eggs. In the PCR amplification of OvNad subunits, there exist 100% specificities with varied sensitivities from 64%, 88%, 80%, and 100% of OvNad1, OvNad2, OvNad4, and OvNad5, respectively. OvNad subunits were amplified specifically without cross reactivity with the other collected parasites. Our study established that OvNad subunits, especially OvNad5, are the potent candidates for PCR amplification of stool containing Ov-eggs with high confidential sensitivity, specificity, PPV, and NPV even in the light infection that would be a benefit for developing as a routine diagnosis of O. viverrini infection.